2012
DOI: 10.5539/jas.v4n2p167
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitrogen and Potassium Fertilizer on Yield and Mineral Accumulation in Flue-Cured Tobacco

Abstract: In order to investigate the effect of nitrogen and potassium fertilizers on yield and mineral accumulation of cv.coker347 and cv.k326 of flue-cured tobacco, 2 year experiment was carried out in tobacco research institute of Rasht located in Guilan province on factorial based with 3 replications. The applied fertilizer levels included 35(N1), 45(N2), 55(N3) and 65 (N4) Kg/ha of pure nitrogen from urea source, and potassium in two levels of 150 (K1) and 200 (K2) Kg/ha potassium from potassium Sulfate. The measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The decline in nutrient uptake and N-and K-recovery efficiency with T 9 might be due to leaching losses of these nutrients to deeper layers beyond root zone due to the porous nature of sandy soils in furrow irrigation, normal seedlings and soil application of fertilizers. Our results confirm with the findings of Farrokh and Farrokh (2012).…”
supporting
confidence: 93%
“…The decline in nutrient uptake and N-and K-recovery efficiency with T 9 might be due to leaching losses of these nutrients to deeper layers beyond root zone due to the porous nature of sandy soils in furrow irrigation, normal seedlings and soil application of fertilizers. Our results confirm with the findings of Farrokh and Farrokh (2012).…”
supporting
confidence: 93%
“…The finding was in agreement with study of Kandil et al (2009) who reported that the increasing trend of basil fresh stem weight as NPK fertilizer rate increased. Farrokh et al (2011) reported that fresh stem weight was increased as N rate increased and the highest weight produced at 65 kg ha-1 N application in tobacco.…”
Section: Fresh Stem Weight Per Plantmentioning
confidence: 99%
“…Meanwhile, the proportion of nitrogen absorbed for nicotine synthesis reached >16% after topping. It caused a significant increase in the nicotine level of tobacco plants [27]. According to [28], topping and suckering improve nicotine level by 59% and reduced sugar by 37% (Table 1).…”
Section: The Benefits Of Topping and Suckeringmentioning
confidence: 99%